Utilization of Solar Heat for the Control of Cowpea Seed Beetle, Callosobruchus Macilatus (Fabricius) (Coleoptera : Bruchidae) - Wessene, Mekasha Chichaybelu (2004)
A survey, consisting of two hundred sample farmers, was conducted in major cool-season food legume growing regions of Ethiopia. Assessment of grain legume seeds collected from sample farmers' stores revealed the importance of adzuki bean beetle, C. chinensis (L.). Storage pests were more serious in mid altitude than highland areas. Farmers realized the negative effect of storage insect pests on marketability, consumption quality and viability of legume seeds. Hence, development of economically feasible and environmentally friendly control options is needed. Biology of C. maculatus was studied on adzuki bean seeds in Malaysia at UPM. Mated female bruchid laid 61.8 eggs on average in its life with reproductive effort of 11.6. Eggs had average incubation period of 4.6 days and mean hatchability rate of 77.9%. Four larval instar stages were recognized. The insect had mean developmental period of 27.8 days with adult emergence rate of 62.0%. Number of eggs had strong negative relation to age of female bruchid while developmental period had positive relation. Obtuse-base-angle box heaters glued from inside with aluminum foil had better ability in trapping solar energy where 118' base-angle box had significantly high performance. Square box heaters painted black from inside trapped higher solar energy with better performance of boxes of 10 cm height, though not as capable as the obtuse-base-angle box heaters. The different glazing thicknesses and glazing layers did not show significant effect on the extent of trapped energy. Box heater of 118' base angle, glued from inside with aluminum foil was, therefore, promoted for further evaluation of the effect of heating on C. maculatus, due to its better performance in trapping solar energy. Effect of heat treatment on C. maculatus and adzuki bean seed moisture content and germination was evaluated. Exposure of the various developmental stages of C. maculatus to heat for up to 45 minutes raised the temperature between and within the seeds well in excess of the lethal level and resulted in complete control. Treatment of adzuki bean seeds with heat for up to one hour did not significantly affect seed viability. Though there was no significant difference, about 18.6% and 27% loss in seed viability resulted from seeds treated for 30 and 60 minutes, respectively, should not be undermined. Hence, adzuki bean seeds meant for planting should not be heat treated to control storage insect pests. However, heat treatment had no much effect on seed moisture content. Assessment on the effect of seed layer thickness on the efficacy of heat treatment against C. maculatus revealed that up to 3 cm thickness of adzuki bean seed can be treated at a time, as neither adult bruchids survived heat treatment nor emerged later. Therefore, solar heating of infested adzuki bean seeds using the aforementioned box heater around noon for an hour can give effective control of C. maculatus.